Research in the sociology of education - Park, Hyunjoon; Kao, Grace (Bingley, UK Emerald Publishing, 2018)
Research in the Sociology of Education is an important and established series, highlighting how societal contexts shape the educational experiences and outcomes of individual children and youth. Including five single-country studies from settings as diverse as rural China, Germany and the United States, as well as two cross-national comparative studies, this insightful new volume continues the series tradition for publishing research from across a broad range of settings. It demonstrates that various educational issues (including student victimization at school, immigrant-native gaps in educational aspiration, and STEM outcomes) are not limited to specific societies but are relevant worldwide. By exploring national and regional situations and then placing them within this broader context, readers are able to see both the commonality and uniqueness of educational issues around the globe -- Provided by the publisher.
Educational outcomes of heterogeneous groups of students in diverse contexts / Hyunjoon Park abd Grace Kao -- The variation in educational aspirations among immigrant students in Germany / Taylan Acar -- School violence in China: a multilevel analysis of student victimization in rural middle schools / Jennifer Adams and Emily Hannum -- Global patterns of the use of shadow education: student, family, and national influences / Soo-yong Byun, Hee Jin Chung and David P. Baker -- Narratives of interdependence and independence: the role of social class and family relationships in where high-achieving students apply to college / Yang Lor -- Jumping on the STEM train: differences in key milestones in the STEM pipeline between children of immigrants and natives in the United States / Yingyi Ma and Amy Lutz -- Socialization experiences and research productivity of Asians and Pacific islanders: "model minority" stereotype and domestic vs. international comparison / Josipa Roksa, Soojeong Jeong, David Feldon and Michelle Maher -- Gender gaps in student academic achievement and inequality / Shu-Ling Tsai, Michael L. Smith and Robert M. Hauser.
Includes bibliographical references and index.
Keywords: Educational sociology